Имагологическая рецепция образа Андрея Штольца в контексте современной исторической эпохи - Isapchuk, Yulia (Brno: Ústav slavistiky FF MU, 2021)
The study analyzes the figure of Andrey Stolz, one of the central characters in the I. A. Goncharovʼs novel “Oblomov” (1859), in the imagological aspect. The Ethno Image “German” is viewed from a panchronic perspective, taking into account national stereotypes and the authorʼs intentions. The article examines the reception of Stolz as an element of Other in the Slavic (Russian) worldview and his adaptability from the XXI century’s perspective. Анализируется фигура Андрея Штольца, одного из центральных персонажей романа И. А. Гончарова «Обломов» (1859), в имагологическом аспекте. Этнообраз «немец» рассматривается на панхроническом срезе с учетом национальных стереотипов и авторских интенций. Исследуется восприятие Штольца как чужеродного элемента славянского (русского) мировоззрения и его адаптивность с позиции ХХI века.
Imagological Reception of the Image of Andrey Stolz in the Context of the Modern Historical Era
Keywords: I. Goncharov; “Oblomov”; Stolz; literary imagology; Ethno Image; national stereotype; German